Validation of a cylindrical phantom for verification of radiotherapy treatments in head and neck with special techniques - Vargas, Nicolás M.; Píriz, Gustavo; García, Marcia; Pérez, Niurka (Revista Brasileira de Física Médica, 2015)
Verification of radiotherapy treatments in head and neck requires, among other things, small volume chambers and a phantom to reproduce the geometry and density of the anatomical structure. New documents from the ICRU (International Comission on Radiation Units & Measurements), Report 83, established the need for quality control in radiotherapy with special techniques such as IMRT (intensity-modulated radiation therapy). In this study, we built a cylindrical acrylic phantom with standing water, containing seven measuring points in the transverse plane and free location (0-20 cm) in the longitudinal plane. These points of measurement are constituted by cavities for the accommodation of the ionization chamber of 7 mm of mayor diameter (semiflex, pinpoint with build cup). The results of the phantom validation yielded percentage differences less than 1% in fixed beams and less than 2.5% in arc therapy for TPS Eclipse calculation. The preparation of this phantom, particularly made to verify the head and neck treatments, was simple and reliable for checking the dose in radiotherapy with fixed beams and/or special techniques such as arc therapy or IMRT, so that will be sent to various radiotherapy centers in the country for dosimetric verification in such treatments.